An intervention using a self-help guide to improve the coping behaviour of nightshift workers and its evaluation - Wedderburn, Zander; Rankin, David (Sudbury, 2001)
"This paper concerns the evaluation of an educational self-help booklet "The Shiftworkers' Guide". A review of the literature has shown that there are common problems attributable to shiftwork including effects on sleep, eating habits, social life, domestic life and exercise patterns. Shiftwork can also be a risk factor leading to the development of adverse health consequences including gastointestinal disease, cardiovascular problems and psychoneurotic disturbance. The Shiftworkers' Guide disseminates advice in the form of coping strategies that aim to alleviate shiftwork problems thus improving adaptation to working shifts and also to ameliorate the negative health effects experienced by shiftworkers.